Vulnerabilidade socioambiental à salinização dos solos na sub-bacia do Riacho do Pontal – semiárido pernambucano do Rio São Francisco - Castro, Francelita Coelho (2024)
Soil salinization, a process involving the accumulation of soluble salts in quantities harmful to the development of non-halophyte plants, is a growing concern, especially in dry climate regions. This phenomenon results from the interaction between natural factors—such as climatic, topographic, geological, and edaphic characteristics—and human activities, notably irrigated agriculture without proper soil and water management. Despite its importance, there is a significant gap in the specific understanding of environmental susceptibility and socio- environmental vulnerability to soil salinization in specific areas, such as the Riacho do Pontal sub-basin in the semiarid region of Pernambuco. Therefore, the purpose and this research is to analyze drainage environmental susceptibility and socio-environmental vulnerability to soil salinization in the said sub-basin, contributing to filling this gap. To achieve this goal, a methodology that includes mapping six physical-natural attributes (lithology, climate, relief, fluvial channels, water, and soils) and one anthropogenic (land use and cover) was adopted. In addition, the local population's socio-environmental vulnerability was assessed, considering access to information on proper soil and water management, family income, and access to financing for agricultural activities. The data were collected from documentary bases of IBGE, IPA, municipal governments, and CPRM. The results revealed that 0.65% of the sub-basin area has very high environmental susceptibility to salinization, while 3.60% presents high susceptibility, 23.70% medium susceptibility, 60.17% low susceptibility, management11.85% very low susceptibility. Regarding socio-environmental vulnerability, 0.07% of the local population has very high vulnerability, 1.06% high vulnerability, 14.84% medium vulnerability, 75.19% low vulnerability, and 8.81% very low vulnerability. The different levels of socio-environmental vulnerability were driven by social factors such as schooling, average family income, access to rural extension policies and accessibility to financing linked to environmental susceptibility to salinization. It is concluded that the Riacho do Pontal sub-basin presents an alert scenario for the soil salinization process, especially in areas with medium environmental susceptibility and medium socio-environmental vulnerability. These areas, close to or within agricultural irrigation zones, require immediate attention for the implementation of public extension policies focused on supporting farmers.